'You need to understand the extent of the bubble we grew up in': The religio‐cultural aspects of sibling's sexual dynamics—Perspectives of Orthodox Jewish adults. Issue 4 (30th March 2022) - Marmor, Amitai; Gemara, Netanel; Lusky‐Weisrose, Efrat; Tener, Dafna
Abstract: The term 'sibling sexual dynamics' (SSD) describes (in this study) a continuum of childhood sexual behaviours that are inconsistent with age‐appropriate curiosity and can include abuse (SSA). The present qualitative study, based on 20 semi‐structured interviews, conducts an analysis via constructivist grounded theory on the perspectives of adults who, as children in the Orthodox Jewish community, experienced sexual interactions with one or more of their siblings. Ultimately, the goal is to deepen the understanding of the religio‐cultural aspects of SSD in this cultural context. The findings reveal three main themes: (1) taboos, both those relating to intrafamilial sexual encounters and the religious taboo around sexuality in general; (2) family hierarchic dynamics, including gender‐based hierarchies; and (3) religious prohibition, a concept that the participants perceive as influencing their modes of thought and logic. The study highlights the need for practitioners to attend to the double ambiguity arising from the sibling and religious contexts. Additionally, we suggest that distinguishing between religious and interpretative socio‐cultural factors may provide practitioners with a path to create a dialogue with clients, individuals and religious leaders within the community around issues that may constitute risk for sibling sexual acts and abuse.